Influence of temperature and strain rate on tensile deformation and fracture behaviour of boron added P91 steel. (March 2019) - Choudhary, B.K.; Christopher, J.
Abstract: Tensile tests were performed at the strain rates ranging from 3.16 × 10 −5 to 1.26 × 10 −3 s −1 over a temperature range 300–873 K to examine the influence of temperature and strain rate on tensile deformation and fracture behaviour of boron added P91 ferritic steel. The variations of flow stress/strength values, work hardening rate and tensile ductility with respect to temperature exhibited three distinct temperature regimes. The steel exhibited anomalous variations in tensile properties due to dynamic strain ageing occurring at intermediate temperatures and the dominance of dynamic recovery at high temperatures. The fracture mode remained transgranular. Presence of large amount of chisel tip appearance along with dimples at 300 K and dominance of ductile dimples at intermediate and high temperatures were observed. Boron added P91 steel with reduced nitrogen exhibited strength values comparable to those reported for the plates and tubes of P91 steel. Highlights: Boron added P91 steel exhibited three temperature regimes. DSA was observed at intermediate temperatures. Dominance of dynamic recovery was observed at high temperatures. Boron added P91 steel with reduced nitrogen exhibited strength values comparable to P91 steel.